Chemotherapy in locally advanced head and neck squamous cell carcinoma. (March 2016) - Gyawali, Bishal; Shimokata, Tomoya; Honda, Kazunori; Ando, Yuichi
Highlights: Chemotherapy has a vital role in all settings of head and neck cancer treatment. Controversies exist on induction chemo versus definitive chemoradiation for LAHNSCC. Controversies also exist on chemoradiotherapy versus cetuximab-radiotherapy. This review tries to answer those controversies based on the very latest evidences. Better planned clinical trials are desperately needed in LAHNSCC. Abstract: Chemotherapy, in combination with a local treatment, has a role in nearly all the settings of locally advanced head and neck squamous cell carcinoma (LAHNSCC) treatment: as definitive, adjuvant or induction therapy. However, despite many years of trials, controversies still exist regarding the best approach to using chemotherapy in the multi-modal treatment of LAHNSCC. Opinions are divided on sequential versus concurrent use of chemotherapy and radiotherapy for unresectable LAHNSCC. More debate exists on whether the addition of induction chemotherapy to concomitant chemoradiotherapy is clinically meaningful. After the approval of cetuximab in combination with radiotherapy for this disease, making treatment choices have become further complicated. Although new data from trials are arriving every year, the results have been inconclusive. In this review, we provide the readers with the latest information on various strategies of using chemotherapy and cetuximab that will help to make an evidence-based decision in the treatment of LAHNSCC, including the approach to larynx preservation. We conclude that with the available information, concurrent chemoradiotherapy should be preferred over induction chemotherapy, except in the setting of larynx preservation. Furthermore, given the paucity of positive data and severe financial toxicity associated with cetuximab, concurrent chemoradiotherapy should be the preferred choice over cetuximab–radiotherapy. Future trials in head and neck cancer should be properly planned to address these controversies and provide clear solutions.